Recent Progress on High‐Performance Cathode Materials for Zinc‐Ion Batteries. Issue 2 (2nd November 2020) - Zhang, Maiwen; Liang, Ruilin; Or, Tyler; Deng, Ya-Ping; Yu, Aiping; Chen, Zhongwei
Abstract : Rechargeable zinc‐ion batteries (ZIBs) have emerged as a contender in the area of electrochemical energy storage applications due to their low cost and inherent safety. To optimize the battery performances, ZIBs cathode materials with high capacity and cyclability have been intensively studied, with most attention focused on traditional manganese‐ and vanadium‐based materials. Recently, other novel cathode materials including Prussian blue analogues (PBAs), polyanions, metal sulfides, and organic compounds have begun to gain recognition as promising alternatives. These materials exhibit distinct strength such as high operating voltage, additional capacity by new redox chemistry activation, and/or highly reversible cycling process that are particularly desirable for ZIBs applications. To provide the highlight they deserve, this review focuses on introducing the recent progresses of these ZIBs cathodes and demonstrating common strategies adopted for material modification and optimization. Finally, systematic comparisons among the cathode materials are analyzed, along with challenges and perspectives on each category of the cathodes. Abstract : High‐performance cathode materials are highly desired to realize the application of zinc‐ion batteries (ZIBs). Herein, working mechanisms of ZIBs cathodes including Prussian blue analogues (PBAs), polyanions, metal sulfides, and organic compounds are introduced. Recent advanced modification methods and innovations are then discussed in detail. Finally, perspectives on further investigations and performance optimizations of cathode materials are provided.